2013
DOI: 10.1371/journal.pone.0060348
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Neuraminidase Inhibitors for the Prevention and Treatment of Seasonal Influenza: A Systematic Review of Systematic Reviews

Abstract: Controversy has arisen regarding the effectiveness of neuraminidase inhibitors (NIs), especially against influenza-related complications. A literature search was performed to critically assess the evidence collected by the available systematic reviews (SRs) regarding the benefits and disadvantages of NIs (oseltamivir, zanamivir) compared to placebos in healthy and at-risk individuals of all ages for prophylaxis and treatment of seasonal influenza. A SR was done using the Cochrane Database of Systematic Reviews… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0
5

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(69 citation statements)
references
References 89 publications
1
63
0
5
Order By: Relevance
“…This finding confirms previous estimates and is comparable with observed effects of oseltamivir 2 4. No treatment effect was seen on pneumonia.…”
Section: Commentarysupporting
confidence: 92%
See 1 more Smart Citation
“…This finding confirms previous estimates and is comparable with observed effects of oseltamivir 2 4. No treatment effect was seen on pneumonia.…”
Section: Commentarysupporting
confidence: 92%
“…Previous systematic reviews (SRs) of zanamivir may have been affected by publication bias and missing data, and clinical recommendations based on such studies should be considered inadequate 1 2. To deal with these shortcomings, this SR and meta-analysis (an update of a Cochrane Review)3 reanalysed the prophylactic and treatment effects of zanamivir on those suffering from influenza, based on the full clinical study reports of all relevant trials provided by the manufacturer and on regulatory comments.…”
Section: Contextmentioning
confidence: 99%
“…Meta-analysis has been used to identify significance and draw conclusions from the numerous and disparate reports of oseltamivir efficacy (Ebell et al, 2013; Jefferson et al, 2012; Michiels et al, 2013; Wang et al, 2012). Unfortunately, these meta-analyses have not delineated NAI treatment for influenza B, but have suggested that oseltamivir is marginally effective in reducing the duration of illness for all influenza infections.…”
Section: Nais For the Control Of Influenza Bmentioning
confidence: 99%
“…The current standard of care is treatment using the neuraminidase inhibitors oseltamivir and zanamivir. It is recommended that treatment begin as early as possible after the onset of illness, ideally within 48 h. The benefit of these agents has recently received considerable scrutiny, with several observational studies reporting reduced mortality in treated individuals during the recent H1N1pdm09 pandemic (17-19) whereas other reviews have questioned this observation (20,21). In addition to the limited treatment window, another concern for this class of antivirals is the possibility of neuraminidase inhibitor resistance, as occurred during the 2008 to 2009 season when oseltamivir-resistant H1N1 was prevalent (22,23).…”
mentioning
confidence: 99%